2003
DOI: 10.1093/carcin/24.3.403
|View full text |Cite
|
Sign up to set email alerts
|

Mammary epithelial cells of PR-A transgenic mice exhibit distinct alterations in gene expression and growth potential associated with transformation

Abstract: Expression of the 'A' and 'B' forms of progesterone receptor (PR), in an appropriate ratio is critical for normal mammary development. As such, mammary glands of PR-A transgenic mice, carrying additional 'A' form of PR as transgene, exhibit morphological and histological characteristics associated with transformation. Accordingly, in the present studies, we analyzed these mammary glands for the presence of transformed epithelial cells by examining for alterations in gene expressions and growth potential, known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
1
11
1
Order By: Relevance
“…While most PR-target genes were not sensitive to the ratio change, progestin responsiveness was acquired in a subpopulation of gene targets involved in a distinct functional role: cell shape and adhesion (Graham et al 2005). Similar findings have been reported for ductal growth and epithelial transformations in mammary glands of transgenic mice carrying a change in the balance of the native ratio of A:B due to overexpression of PR-A (Shyamala et al 2000, Chou et al 2003.…”
Section: Gnrh Priming In Wild Type Mouse Gonadotropes In Vitro (Turgesupporting
confidence: 60%
“…While most PR-target genes were not sensitive to the ratio change, progestin responsiveness was acquired in a subpopulation of gene targets involved in a distinct functional role: cell shape and adhesion (Graham et al 2005). Similar findings have been reported for ductal growth and epithelial transformations in mammary glands of transgenic mice carrying a change in the balance of the native ratio of A:B due to overexpression of PR-A (Shyamala et al 2000, Chou et al 2003.…”
Section: Gnrh Priming In Wild Type Mouse Gonadotropes In Vitro (Turgesupporting
confidence: 60%
“…Rose showed that mutation of the p53 gene was associated with the absence of PR [4]. Also, Chou et al reported that cyclin D1 expression was up-regulated in mammary epitherial cells in PR-A transgenic mice [34]. However, cyclin D1 expression was inversely correlated with PR-A in our study.…”
Section: Discussioncontrasting
confidence: 40%
“…BrdU-positive cells were analyzed in paraffin-embedded sections as described previously [9]. Briefly, paraffin sections were deparaffinized and rehydrated prior to antigen retrieval and treatment with specified antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…Studies using the molecular markers for transformation, as defined by Medina [8], revealed that these mammary glands contained at least two distinct populations of transformed epithelial cells. The ducts with normal histology contain cells resembling immortalized cells, while hyperplasias consist of cells in later stages of transformation associated with early preneoplasias [9]. …”
Section: Introductionmentioning
confidence: 99%